A Note on Definitions of Related Goods - Morishima, M. (Review of Economic Studies, 1955)
Journal Article A Note on Definitions of Related Goods Get access M. Morishima M. Morishima Osaka Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 23, Issue 2, 1955, Pages 132–134, https://doi.org/10.2307/2296296 Published: 01 January 1955